Inflammation is independent of steatosis in a murine model of steatohepatitis - Wang, Wei; Xu, Ming‐Jiang; Cai, Yan; Zhou, Zhou; Cao, Haixia; Mukhopadhyay, Partha; Pacher, Pal; Zheng, Shusen; Gonzalez, Frank J.; Gao, Bin (Hepatology (Baltimore, Md.), 2017)
Obesity and alcohol consumption synergistically promote steatohepatitis, and neutrophil infiltration is believed to be associated with steatosis. However, the underlying mechanisms remain obscure. Peroxisome proliferator–activated receptor gamma (PPARγ) plays a complex role in lipid metabolism and inflammation; therefore, the purpose of this study was to dissect its role in regulating steatosis and neutrophil infiltration in a clinically relevant mouse steatohepatitis model of 3‐month high‐fat diet (HFD) feeding plus a binge of ethanol (HFD‐plus‐binge ethanol). Hepatocyte‐specific Pparg disruption reduced liver steatosis but surprisingly increased hepatic neutrophil infiltration after HFD‐plus‐binge ethanol. Knockout or knockdown of the PPARγ target gene, fat‐specific protein 27, reduced steatosis without affecting neutrophil infiltration in this model. Moreover, hepatocyte‐specific deletion of the Pparg gene, but not the fat‐specific protein 27 gene, markedly up‐regulated hepatic levels of the gene for chemokine (C‐X‐C motif) ligand 1 (Cxcl1, a chemokine for neutrophil infiltration) in HFD‐plus‐binge ethanol‐fed mice. In vitro, deletion of the Pparg gene also highly augmented palmitic acid or tumor necrosis factor alpha induction of Cxcl1 in mouse hepatocytes. In contrast, activation of PPARγ with a PPARγ agonist attenuated Cxcl1 expression in hepatocytes. Palmitic acid also up‐regulated interleukin‐8 (a key chemokine for human neutrophil recruitment) expression in human hepatocytes, which was attenuated and enhanced by cotreatment with a PPARγ agonist and antagonist, respectively. Finally, acute ethanol binge markedly attenuated HFD‐induced hepatic PPARγ activation, which contributed to the up‐regulation of hepatic Cxcl1 expression post–HFD‐plus‐binge ethanol. Conclusion: Hepatic PPARγ plays an opposing role in controlling steatosis and neutrophil infiltration, leading to dissociation between steatosis and inflammation; acute ethanol gavage attenuates hepatic PPARγ activation and subsequently up‐regulates hepatic CXCL1/interleukin‐8 expression, thereby exacerbating hepatic neutrophil infiltration. (Hepatology 2017;66:108–123).